Step‐Gradient Composite Hydrogels for Local Drug Delivery and Directed Cell Migration. Issue 9 (9th July 2021) - Motealleh, Andisheh; Kehr, Nermin S.
Abstract : Even though remarkable advances in biomedical engineering have been made in recent decades, fabricated biomaterials as artificial tissue constructs still have room for improvement and need to offer several characteristics simultaneously. Specifically, engineered biomaterials should possess mechanical, biochemical, and topographical gradients, a 3D network, porosity, biocompatibility, biodegradability, and injectability as well as the ability to deliver drugs locally, to mimic the extracellular matrix environment, to control directional cell migration, to promote vascularization of implanted tissue constructs, to inhibit inflammation after implantation, and to be implanted in a minimally invasive manner. In this respect, a new step‐gradient composite hydrogel and scaffold (GradGA) fabricated by a 3D bioprinting technique is created. This GradGA material is constructed using different ratios of multifunctional porous nanomaterials (NMs), alginate, and gelatin methacryloyl, where the multifunctional NMs allowed for sustained and pH‐responsive controlled release of anti‐inflammatory and chemotherapeutic drug molecules within the 3D network of the composite hydrogel. Further, the construction promotes healthy cell viability and migration in the XY plane of GradGA, whereas it reduces the migration and growth of cancer cells due to the pH‐responsive release of chemotherapeutic drug molecules. Abstract : A new 3D step‐gradient composite hydrogel and scaffold (GradGA) generated by using pH‐responsive nanomaterials and different hydrogel composites for improved healthy cell viability, controlled directional cell migration, and reduced cancer cell viability is described.